Peran Ustadz dan Pengurus dalam Meningkatkan Prestasi Santri Pondok Pesantren - Huda, Nurul (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2023)
This research was conducted at the Miftahul Ulum Islamic Boarding School, Kareteng, Bawean Island. The aim is to 1) Know the role of Ustadz and Islamic boarding school administrators in improving the achievements of Islamic boarding school students, and 2) Understand the role of Islamic boarding school administrators in improving the achievements of Islamic boarding school students. The research method used is a qualitative method, while the data collection techniques used are observation, interviews and documentation techniques, data analysis techniques used; data reduction, data presentation, and data verification, and data checking using triangulation of sources, techniques, and time. The results show that 1) The role of the Ustadz in improving the achievement of students by providing tutoring such as compulsory learning from 08:00-09:00, holding special coaching such as tutoring for students for 30 minutes starting from 10:00 - 10:30, and holding evaluations every six months. 2) The role of Islamic boarding school administrators in improving students at the Miftahul Ulum Kareteng Islamic boarding school by collaborating internally and externally and deliberating between all Islamic boarding school administrators once a month to combine work programs so that they are carried out well.